إجراءات تقریر المسؤولیة السیاسیة للوزارة وآثارھا في النظام البرلماني: دراسة مقارنة - شبر، رافع خضر صالح; الجراحي، كريم لفته مشاري (جامعة بابل - كلية القانون, 2015)
The Cabinet in charge of the parliamentary system is characterized as being based on the confidence of Parliament, any obligation to acquire the ministerial council's formed after the elections the confidence of the council of Representatives as a prerequisite for taking office. by taking over the cabinet of power, they would be responsible in the aggregate policy pursued by the front of the parliament, and this responsibility had to resign the ministry as a whole as long as the act which enjoined responsibility connected policy of the Public Ministry, but if the disposition of a special minister in particular or the ministers specific terms of the act, which moving on the basis of which is attributed to the Minister of specific and particular his policy is not the policy of the Council of Ministers the responsibility here be individualized, but the political responsibility of the ministry is not moving automatically, but there are procedures, whereby moving this responsibility, then the withdrawal of confidence from the ministry and it's drop. Exciting political responsibility indictment by the Parliament of the ministry as a group or members, including negligence, and a vote of confidence as a request to condemn the ministry (or minister) to shorten the decision to withdraw confidence is the rule of the ministry or the minister not to the validity of political, The report of the responsibility of the ministry and the withdrawal of confidence in most cases, not be without that preceded a damning indictment by the Parliament of the ministry as a group or members of negligence of them and discuss the charge. Constitutions have agreed that the consequence of the withdrawal of confidence from the ministry or the minister responsible is resign. The aim of the research to identify how they were organizing procedures move the political responsibility of the Ministry and their implications constitutionally and legislatively in light of what he quoted the legislator of the principles of the parliamentary system, and the extent of matching the constitutional provisions concerning the procedures and the effects of the political responsibility of the ministry with the practical reality, There are several problems theory has been searched, including empty of Constitution to address some aspects of the procedures for the political responsibility of the ministry, and the constitutionality of the legal rules that have addressed some aspects of the political responsibility of the ministry by anonymous on processed constitution.
الوزارة المسؤولة في النظام البرلماني تتسم بأنها تستند إلى ثقة البرلمان، أي وجوب أن تحوز الوزارة المشكلة بعد الانتخابات على ثقة المجلس النيابي كشرط مسبق لتوليها الحكم. وخلال تولي الوزارة السلطة، فإنها تكون مسؤولة في مجموعها عن السياسة العامة التي تنتهجها أمام البرلمان، وهذه المسؤولية توجب استقالة الوزارة بأسرها طالما كان التصرف الذي أوجب المسؤولية متصلاً بسياسة الوزارة العامة، أما إذا كان التصرف خاصا بوزير بالذات أو على وزراء محددين حيث يكون الفعل الذي تتحرك على أساسه منسوباً إلى وزير معين وخاصاً بسياسته هو لا بالسياسة العامة لمجلس الوزراء فإن المسؤولية هنا تكون فردية، وإن المسؤولية السياسية للوزارة لا تتحرك ذاتيا وإنما هناك إجراءات، يتم بموجبها تحريك هذه المسؤولية، ثم سحب الثقة من الوزارة وإسقاطها. وإن إثارة المسؤولية السياسية اتهام صريح من قبل البرلمان للوزارة كمجموعة أو لأعضاء منها بالتقصير، وطرح الثقة بمثابة طلب إدانة الوزارة (أو الوزير) على تقصيرها وقرار سحب الثقة هو حكم على الوزارة أو الوزراء بعدم الصلاحية السياسية، وإن تقرير المسؤولية للوزارة وسحب الثقة منها في معظم الحالات، لا يكون دون أن يسبقه اتهام صريح من قبل البرلمان للوزارة كمجموعة أو لأعضاء منها بالتقصير ومناقشة هذا الاتهام. وقد اتفقت الدساتير على أن النتيجة المترتبة على سحب الثقة من الوزارة أو الوزير المسؤول هي الاستقالة. وإن الهدف من البحث هو للتعرف على الكيفية التي تم بها، تنظيم إجراءات تحريك المسؤولية السياسية للوزارة والآثار المترتبة عليها دستورياً وتشريعيا، في ظل ما اقتبسه المشرع من مبادئ النظام البرلماني، ومدى مطابقة النصوص الدستورية التي تخص إجراءات وآثار المسؤولية السياسية للوزارة مع الواقع العملي، وهنالك عدة إشكاليات نظرية تم البحث فيها ، منها سكوت الدستور عن معالجة بعض جوانب إجراءات المسؤولية السياسية للوزارة ، ومدى دستورية القواعد القانونية التي عالجت بعض جوانب المسؤولية السياسية للوزارة التي غفل عن معالجتها الدستور.
Keywords: القوانين والتشريعات -- النظام البرلماني -- المسؤولية السياسية -- المجلس النيابي -- الدستور -- التشريع القانوني -- مستخلصات الأبحاث